Enhanced CO2 separation performance for tertiary amine‐silica membranes via thermally induced local liberation of CH3Cl. Issue 5 (7th December 2017) - Yu, Liang; Kanezashi, Masakoto; Nagasawa, Hiroki; Moriyama, Norihiro; Tsuru, Toshinori; Ito, Kenji
Abstract : A facile method for the fabrication of amine‐silica membranes with enhanced CO2 separation performance was proposed via the thermally induced liberation of small molecules from quaternary ammonium salt. Quaternary ammonium‐silica (QA‐SiO1.5 ) xerogel powders/films were fabricated via sol‐gel processing and their thermal stability was systematically studied using thermogravimetric mass spectrometer, Fourier transform infrared, energy dispersive spectroscopy, and positron annihilation lifetime spectroscopy analysis. CO2 sorption performances of QA‐SiO1.5 derived xerogel powders were quantitatively compared after assigning their relevant parameters to a dual‐mode sorption model. The gas permeation performances of membranes derived from QA‐SiO1.5 were evaluated in terms of kinetic diameter and temperature dependence of gas permeance, and activation energy (Ep ) required for gas permeation. The results indicate that liberation of the CH3 Cl molecules from these membranes significantly improved both CO2 permeation and CO2 /N2 separation capabilities. Therefore, the present study provides insight that should be useful in the development of high‐performance CO2 separation membranes via the effect of the thermally induced liberation of small molecules. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1528–1539, 2018